Incidence and determinants of extrapulmonary tuberculosis in Egypt: a retrospective cohort study - Wagdy Amin; Rasha Ashmawy; Sarah Assem Ibrahim; Yousra A. El-Maradny; Neamat Hamdy Elsawy; Shaimaa Abdallah Gebili; Nahla Gamaleldin; Ramy Mohamed Ghazy (Scientific Reports)
Abstract Tuberculosis (TB) is a significant global public health concern. The incidence of extrapulmonary tuberculosis (EPTB) is increasing; however, comprehensive data on its epidemiological and clinical characteristics remain limited, especially among populations who are co-infected with human immunodeficiency virus (HIV) or hepatitis C virus (HCV). This study aimed to assess the incidence and predictors of EPTB in patients co-infected with HIV or HCV in Egypt. We conducted a retrospective cohort study on patients infected with TB who are treated in Egyptian chest hospitals from January 1 to December 31, 2023. Patients were categorized into pulmonary TB (PTB) and EPTB. Clinical data, including HIV or HCV co-infection status, were analyzed to identify risk factors and comorbidities associated with EPTB. Multilevel logistic regression was employed to examine predictors of EPTB. Among 7,245 TB patients, 42.5% were diagnosed with EPTB. Determinant of EPTB were HIV-positive (OR = 0.46, 95% CI: 0.30–0.71, p < 0.001), being male (OR = 0.31, 95% CI: 0.27–0.35, p < 0.001 ), age (particularly children under 5 years) (OR = 4.75, 95% CI: 2.29–9.84, p < 0.001 ), urban residency (OR = 1.05, 95% CI: 0.87–1.27, p < 0.05), and comorbidities (OR = 0.59, 95% CI: 0.35–0.98, p < 0.05). The most common sites for EPTB were the lymph nodes (27.10%) and pleural cavity/effusion (24.60%). EPTB represents a substantial proportion of TB cases in Egypt, particularly among younger individuals and females. Despite the low percentage of HIV or HCV co-infection in EPTB cases, further analysis and diagnostic testing of undiagnosed patients are required. These findings underscore the need for targeted interventions and comprehensive care models for TB patients, especially in the context of HIV co-infection.